If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(2x + 1) = (x + 6)(2x + 3) Reorder the terms: (2 + x)(2x + 1) = (x + 6)(2x + 3) Reorder the terms: (2 + x)(1 + 2x) = (x + 6)(2x + 3) Multiply (2 + x) * (1 + 2x) (2(1 + 2x) + x(1 + 2x)) = (x + 6)(2x + 3) ((1 * 2 + 2x * 2) + x(1 + 2x)) = (x + 6)(2x + 3) ((2 + 4x) + x(1 + 2x)) = (x + 6)(2x + 3) (2 + 4x + (1 * x + 2x * x)) = (x + 6)(2x + 3) (2 + 4x + (1x + 2x2)) = (x + 6)(2x + 3) Combine like terms: 4x + 1x = 5x (2 + 5x + 2x2) = (x + 6)(2x + 3) Reorder the terms: 2 + 5x + 2x2 = (6 + x)(2x + 3) Reorder the terms: 2 + 5x + 2x2 = (6 + x)(3 + 2x) Multiply (6 + x) * (3 + 2x) 2 + 5x + 2x2 = (6(3 + 2x) + x(3 + 2x)) 2 + 5x + 2x2 = ((3 * 6 + 2x * 6) + x(3 + 2x)) 2 + 5x + 2x2 = ((18 + 12x) + x(3 + 2x)) 2 + 5x + 2x2 = (18 + 12x + (3 * x + 2x * x)) 2 + 5x + 2x2 = (18 + 12x + (3x + 2x2)) Combine like terms: 12x + 3x = 15x 2 + 5x + 2x2 = (18 + 15x + 2x2) Add '-2x2' to each side of the equation. 2 + 5x + 2x2 + -2x2 = 18 + 15x + 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 2 + 5x + 0 = 18 + 15x + 2x2 + -2x2 2 + 5x = 18 + 15x + 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 2 + 5x = 18 + 15x + 0 2 + 5x = 18 + 15x Solving 2 + 5x = 18 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 2 + 5x + -15x = 18 + 15x + -15x Combine like terms: 5x + -15x = -10x 2 + -10x = 18 + 15x + -15x Combine like terms: 15x + -15x = 0 2 + -10x = 18 + 0 2 + -10x = 18 Add '-2' to each side of the equation. 2 + -2 + -10x = 18 + -2 Combine like terms: 2 + -2 = 0 0 + -10x = 18 + -2 -10x = 18 + -2 Combine like terms: 18 + -2 = 16 -10x = 16 Divide each side by '-10'. x = -1.6 Simplifying x = -1.6
| 18w=234 | | -27=-7w+4(w-6) | | 4y^2-8y+9=0 | | 14-(5x-6)=-6(x+1)-5 | | (x+1)(x-3)=4 | | [x]=7 | | 4(2x+3)=6(x+3) | | 8=2v+6 | | .5(1-2.5y)+1.25y=.5 | | -17=n/4-13 | | .8(3v-2w)+.2(7v-2w)= | | 3y=7+5 | | -9y-3=-8y-7 | | 11x+8=4x-6 | | 5w^2+41w+42=0 | | n+15=30 | | 8+13=-3(7x-7) | | 5(5t-2)=-36 | | 9x+1=46 | | -4(y-3)=6y-7 | | m/6=-9 | | .5x+1.25y=.5 | | n+15=23 | | 8+13=3(7x-7) | | -(3x-5y)-8(2x+y)= | | -2.35+6.75=-2.18 | | (a^3b)(ab^3)= | | 0.667(6x-15)=0.75(8x+12) | | 5r-13-6r=3(r+5)-16 | | x+15=0 | | -3(4+h)+3h=9-6(h+7) | | 0.12x+1.6=0.66 |